Extracranial Jugular Foramen Schwannomas Treated with the Extreme Lateral Juxtacondylar Approach: Surgical Technique and Our Experience. Issue 4 (12th April 2023) - Di Vitantonio, Hambra; Tozzi, Alessandro; De Paulis, Danilo; Millimaggi, Daniele F.; Di Cola, Francesco; Raysi Dehcordi, Soheila; Galzio, Renato J.; Ricci, Alessandro
Abstract : BACKGROUND: Schwannoma that arises in the jugular foramen (JF) represents an important challenge for neurosurgeons for its precise location, extension, and neurovascular relationship. Nowadays, different managements are proposed. In this study, we present our experience in the treatment of extracranial JF schwannomas (JFss) with the extreme lateral juxtacondylar approach (ELJA). OBJECTIVE: To present our experience in the treatment of extracranial JF schwannomas (JFss) with the ELJA. METHODS: Between January 2013 and January 2017, 12 patients with extracranial JFs underwent surgery by ELJA. All lesions were type C of the Samii classification. Indocyanine green videoangiography was used to evaluate the relationship between the internal jugular vein and the tumor and to control the presence of spasm in the vertebral artery. RESULTS: A complete exeresis was achieved in 9 patients while in 3 patients, it was subtotal. The complete regression of symptoms was obtained in 7 patients with a total resection. The remaining cases experienced a persistence of symptoms. CONCLUSION: The success of this surgery is achieved through a management that starts from the patient's position. We promote an accurate evaluation of JFs through the Samii classification: Type C tumors allow the use of ELJA that reduces surgical complications. Furthermore, we recommend the use of indocyanine green videoangiography to preserve the vessels and prevent vasospasm.